The heat shock protein 90 of Plasmodium falciparum and antimalarial activity of its inhibitor, geldanamycin - Kumar, Rajinder (BioMed Central, 2003)
BACKGROUND: The naturally occurring benzoquinone ansamycin compound, geldanamycin (GA), is a specific inhibitor of heat shock protein 90 (Hsp90) and is a potential anticancer agent. Since Plasmodium falciparum has been reported to have an Hsp90 ortholog, we tested the possibility that GA might inhibit it and thereby display antiparasitic activity. RESULTS: We provide direct recombinant DNA evidence for the Hsp90 protein of Plasmodium falciparum, the causative agent of fatal malaria. While the mRNA of Hsp90 was mainly expressed in ring and trophozoite stages, the protein was found in all stages, although schizonts contained relatively lower amounts. In vitro the parasitic Hsp90 exhibited an ATP-binding activity that could be specifically inhibited by GA. Plasmodium growth in human erythrocyte culture was strongly inhibited by GA with an IC(50 )of 20 nM, compared to the IC(50 )of 15 nM for chloroquine (CQ) under identical conditions. When used in combination, the two drugs acted synergistically. GA was equally effective against CQ-sensitive and CQ-resistant strains (3D7 and W2, respectively) and on all erythrocytic stages of the parasite. CONCLUSIONS: Together, these results suggest that an active and essential Hsp90 chaperone cycle exists in Plasmodium and that the ansamycin antibiotics will be an important tool to dissect its role in the parasite. Additionally, the favorable pharmacology of GA, reported in human trials, makes it a promising antimalarial drug.